Improving the effectivness of audit committee: a comparative analysis of audit committee codes in US, UK and Egypt - Sarsam, Auday Sabri Tawfeek (AUC Knowledge Fountain, 2010)
The audit committee performs a very important role in corporate governance. The main objective of this research is to enhance the audit committee effectiveness through, a comparison between codes and regulations of the Audit Committee in the U.K., U.S.A. and Egypt. Such comparison will highlight important issues related to Audit Committee activities and will result in modification to the existing Egyptian Code of Corporate Governance for Audit Committee. The importance of the research comes from the fact that the Audit Committee report became mandatory starting from 2009 for all listed companies in the EGX. The study conducted analyzed requirement in the British UK Code, The AICPA Audit Committee Toolkit: Public Companies and other research. Four hypotheses were developed and tested to assess the effect of Audit Committee characteristics including establishment and role, resources, skills and experience, Audit Committee relation with Board of Directors, financial reporting, internal control, whistle-blowing, internal audit function, external audit, annual audit cycle, and communication with shareholders on the effectiveness of the Audit Committee. For this reason, a survey was conducted to analyze the opinion of professionals like AC members, Accountants and Auditors, and the scholars in the education field for the improvement of Audit Committee in Egypt Code of Corporate Governance. Once data were collected, they were analyzed with the statistical software SPSS for implication for Egypt Code of Corporate Governance for Audit Committee. The data subjected to statistical analysis and procedures, including descriptive statistics, frequencies, percentages, mean, correlations and coefficient of variation. The overall analysis of the data gathered was strongly supportive of the 4 hypotheses. The researcher reached a conclusion, referring that, the regulatory initiative has a strong impact on the development of the Corporate Governance Code to be more comprehensive and detailed, on the road, to a proactive and more effective Audit Committee, which will empower the local investment environment and sustain higher rates of economic growth. The researcher recommends the deployment of the proposed provisions by the Egyptian Financial Supervisory Authority with continuous review of the Corporate Governance regulations every three years to catch up with the latest developments relative to the issue.